Relationship Between Educational Justice and Academic Burnout in Medical Interns - Arash Malakian; Mehdi Sayyah; Kowsar Motamed (Baqiyatallah University of Medical Sciences, 2020)
Background: Poor teaching and lack of proper relations between teacher and student and various other causes affect students' academic burnout. Objectives: Present study was conducted to determine the relationship between educational justice and academic burnout in medical interns of Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran. Methods: This study was descriptive and analytical. The number of samples was equal to 300 medical interns identified and entered by the census sampling method. Data were completed by two questionnaires (researcher-made educational justice and burnout standard) whose reliability and validity were confirmed. Data were analyzed by SPSS Version 22. Results: There was no significant relationship between educational justice and academic burnout (P>0.05). Also, educational justice was below average and academic burnout was above average. There was a significant relationship between educational justice score and gender (P < 0.05), and there was no critical relationship with other demographic variables (P>0.05). There was no significant relationship between academic burnout score and all demographic variables (P>0.05). Conclusion: This study concluded that causes other than educational justice have been influential on students' academic burnout. Hence, it suggested that studies be conducted on high academic burnout and identify influential variables. On the other hand, although the relationship between the two variables was not significant, due to the low level of educational justice, the university's need for fair educational opportunities, especially professors, should be considered.